2017
DOI: 10.2147/ijnrd.s108045
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease-associated pruritus: impact on quality of life and current management challenges

Abstract: Chronic kidney disease-associated pruritus (CKD-aP) is a distressing, often overlooked condition in patients with CKD and end-stage renal disease. It affects ~40% of patients with end-stage renal disease and has been associated with poor quality of life, poor sleep, depression, and mortality. Prevalence estimates vary based on the instruments used to diagnose CKD-aP, and standardized diagnostic instruments are sorely needed. Treatment studies have often yielded conflicting results. This is likely related to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
93
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 102 publications
(142 reference statements)
4
93
2
2
Order By: Relevance
“…For duration, 91.4% of the patients reported < 6 h/day. For degree, 63.1% reported mild or more severe itchiness, which is comparable to the 60-80% previously reported [1][2][3][4][5][6][7][8]. However, 14.3% of the patients in our study reported moderate or more severe itchiness, which was lower than the 30-50% previously reported [1][2][3][4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…For duration, 91.4% of the patients reported < 6 h/day. For degree, 63.1% reported mild or more severe itchiness, which is comparable to the 60-80% previously reported [1][2][3][4][5][6][7][8]. However, 14.3% of the patients in our study reported moderate or more severe itchiness, which was lower than the 30-50% previously reported [1][2][3][4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 55%
“…Approximately 60-80% of patients undergoing hemodialysis have pruritus, and many cases are refractory to treatment [1][2][3][4][5][6][7][8]. Moreover, degree of itchiness and sleep disorders are strongly correlated.…”
Section: Introductionmentioning
confidence: 99%
“…It can be acute or chronic, resulting from xerosis or eczema, cirrhosis, hematologic disorders, infection, or drug reactions. Pruritus is one of the most distressing symptoms in chronic kidney disease (CKD) [2] also termed, "CKD associated pruritus" (CKD-P) [3]. Uremic pruritus is extremely common in patients undergoing hemodialysis [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…11 These complications include hyperphosphatemia, which increases the risk of cardiovascular events, bone mineral disorders, secondary hyperparathyroidism, 12 sleep disorders 13 and pruritus, impacting HRQOL in several dimensions. 14 Given the above, it is emphasized that the nurse in a Renal Unit has competence and concrete possibilities to intervene with these patients, in order to provide knowledge that favors adherence to treatment, reducing the harmful effects of the disease on the body and the evaluation of their HRQoL. Among the activities that nurses can perform are educational nursing interventions.…”
Section: Introductionmentioning
confidence: 99%